Les mères de jumeaux en situation de mendicité à Ouagadougou - Aude Nikiema; Honorine Pegdwendé Sawadogo (EchoGéo)
Twinning is an exceptional phenomenon in West Africa. Both feared and revered, in Burkina Faso, twins are at the centre of various ritual practices depending on socio-cultural groups. The example of the twin presentation ritual is illustrative; a mandatory, symbolic and punctual ritual, once prescribed for any mother of twins, of taking her children to a public square to present them to the community and obtain their alms for the protection of children. Nowadays, "twin mothers" beg daily, and for a much longer period of time than tradition prescribes, in the city of Ouagadougou. This article aims to describe the preferential sites occupied by these women and seeks to understand and explain the logic of occupying these places.